Insight perspectives of thermostable endoglucanases for bioethanol production: A review. (July 2018) - Akram, Fatima; Haq, Ikram ul; Imran, Wafa; Mukhtar, Hamid
Abstract: Currently, production of bioenergy has received much attention because it offers a mean to reduce dependence on natural crude oil and to reduce emissions of greenhouse gases which affect our environment globally. Thermotolerant cellulolytic enzymes can hydrolyze the cellulosic polymer chiefly for the production of bioethanol as a second generation fuel and are now being used in many biotechnological fields. Among cellulases, endoglucanase enzyme has been studied and reviewed from various sources and their expression within plants is a futuristic approach that has recently come into focus. Thermostability and solvent-tolerant endoglucanases are highly valuable tools for versatile industrial processes. The structural and sequential properties responsible for endoglucanase heat stability have been scrutinized by many researchers. Here, we have attempted to identify those factors which concern the thermophilic behavior of endoglucanases both individually and synergistically along with other factors, to increase endoglucanase expression and specific activity under favorable conditions. Additionally, we look at the prospect of in-planta expression of endoglucanase as a means to produce cheap and abundant biocatalyst for various industrial and biotechnological applications. Highlights: Bioethanol from waste biomass as an attractive renewable source of energy. Thermostable endoglucanases have garnered relatively more attention as compare to mesozymes. Some molecular features are responsible for increase thermostability of endoglucanase. Thermostable and novel endoglucanases can improve efficiency of biodegradation process of biomass.